Headache - Robbins, Matthew S.; Grosberg, Brian M.; Lipton, Richard B. (Chichester, West Sussex : Wiley Blackwell, 2013)
This book is a practical guide to headache medicine designed for both neurologists and general practitioners. Its expert author team introduces the principles of classification and diagnosis, and focuses in detail on the main classes of headache migraine, tension-type and trigeminal autonomic cephalgias, including cluster headache. The book's clinically focused practical approach covers unusual headache disorders, such as hemicrania continua and new daily persistent headache, and addresses the management of headache in women, children and the elderly.
Part 1: Principles of Headache: Primary and Secondary Headache Disorders 1 The Basics of Headache Classification and Diagnosis / Seymour Solomon and Richard B. Lipton -- 2 Approach to the Patient with Headache / Brian M. Grosberg, Benjamin W. Friedman and Seymour Solomon -- 3 Secondary Headache Disorders Encountered in Clinical Practice / Deborah I. Friedman Part 2: Migraine 4 Diagnosis and Subtypes of Migraine / Seymour Solomon and Brian M. Grosberg -- 5 Epidemiology, Progression, Prognosis, and Comorbidity of Migraine / Richard B. Lipton, C. Mark Sollars and Dawn C. Buse -- 6 Pathophysiology and Genetics of Migraine / Peter J. Goadsby -- 7 Multidisciplinary Approach to Patients with Migraine / Lucille A. Rathier, Dawn C. Buse, Robert A. Nicholson and Frank Andrasik -- 8 Acute Treatments for Migraine / Dagny Holle and Hans-Christoph Diener -- 9 Preventive Treatments of Migraine / William B. Young 10 Managing the Special Problem of Chronic Migraine / Marcelo E. Bigal Part 3: Tension-type Headache 11 Diagnosis, Subtypes, Epidemiology, Progression, Prognosis, and Comorbidity of Tension-type Headache / Sara C. Crystal, Uri Napchan and Matthew S. Robbins -- 12 Pathophysiology and Genetics of Tension-type Headache / Sait Ashina and Lars Bendtsen -- 13 Treatment of Tension-type Headache / Sara C. Crystal and Katherine A. Henry Part 4: Trigeminal Autonomic Cephalgias Including Cluster Headache -- 14 Diagnosis and Subtypes of Trigeminal Autonomic Cephalgias / Arne May 15 Epidemiology, Progression, Prognosis, and Comorbidity of Trigeminal Autonomic Cephalgias / Matthew S. Robbins and Jessica Ailani -- 16 Pathophysiology and Genetics of Trigeminal Autonomic Cephalgias / Peter J. Goadsby -- 17 Treatment of Trigeminal Autonomic Cephalgias including Cluster Headache / Sarah Vollbracht and Brian M. Grosberg Part 5: Other Headache Disorders 18 New Daily-persistent Headache / Matthew S. Robbins -- 19 Hemicrania Continua / Uri Napchan -- 20 Unusual Short Duration Primary Headaches / Sarah Vollbracht and Brian M. Grosberg Part 6: Management of Headache in Specific Patient Populations 21 Management of Headache in Women / Elizabeth W. Loder, Dawn C. Buse, Vincent Martin, Luzma Cardona, Dawn A. Marcus -- 22 Management of Headache in Children / Oranee Sanmaneechai and Karen Ballaban-Gil -- 23 Management of Headache in the Elderly / Matthew S. Robbins and Richard B. Lipton.
Edition statement from running title area.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed August 14, 2013).
Keywords: Headache -- Diagnosis; Headache -- Treatment; Headache Disorders; Headache -- Diagnosis; Headache disorders; Headache; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Headache -- Diagnosis; Headache -- Treatment; Electronic books; Electronic books